Finanças comportamentais: uma avaliação crítica da moderna teoria de finanças - Anache, Marcelo de Carvalho Azevedo (2008)
Among the main commonly debated questions regarding finance, there is the validity of its most traditional theories premises, in special the rationality of economic agents. In this context, different studies have appeared with the intention of improving the theoretical dominant models, incorporating behavioral aspects never considered before. Such innovations gave origin to a new and promising field of study, known as Behavioral Finance. The considerable growth of this non orthodox approach has been motivated, specially, by the attempt to satisfactorily explain a whole gamma of phenomena, commonly observed in financial markets, which are incompatible with traditional models predictions. The main objective of this dissertation is to show the evolution of classical finance studies to, later, inquiry about the explanation of most of the recurring anomalies present in financial markets, which aren t fully understood by means of conventional finance models. One of the emphasis of this work is on fundamental concepts of the still incipient Behavioral Finance paradigm, with the purpose of a more accurate understanding of existing models